Transfer of Buddhism Across Central Asian Networks (7th to 13th Centuries) - Meinert, Carmen (Dynamics in the History of Religions, 2015)
Transfer of Buddhism across Central Asian Networks (7th to 13th Centuries), ed. Carmen Meinert, offers a transregional and transcultural vision for religious transfer processes in Central Asian history. It explores Buddhist localisations in the Tarim basin, the Transhimalaya and Tibet.; Readership: All interested in an interdisciplinary approach towards understanding religious transfer processes across a Central Asian Buddhist network, best known as the Silk Road(s).